The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1016/j.palaeo.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Climate and humans set the place and time of Proboscidean extinction in late Quaternary of South America

Abstract: The late Quaternary extinctions have been widely debated for a long time, but the varying magnitude of human vs. climate change impacts across time and space is still an unresolved question. Here we assess the geographic range shifts in response to climate change based on Ecological Niche Models (ENMs) and modeled the timing for extinction under human hunting scenario, and both variables were used to explain the extinction dynamics of Proboscideans during a full interglacial/glacial cycle (from 126 ka to 6 ka)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 98 publications
(154 reference statements)
1
24
0
1
Order By: Relevance
“…However, in spite of their predicted expansion, those species disappeared from Europe. Thus, our results indicate that not all the mammal extinctions in Europe can be directly linked to past global climatic changes (Varela et al ., ; Lima‐Ribeiro et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in spite of their predicted expansion, those species disappeared from Europe. Thus, our results indicate that not all the mammal extinctions in Europe can be directly linked to past global climatic changes (Varela et al ., ; Lima‐Ribeiro et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These studies suggest that both global climate change and human impact played key roles in observed species extinctions. Climate warming could have led to the shrinkage of species' geographic ranges, and humans may have impacted the remaining, reduced populations (Nogues‐Bravo et al ., ; Lima‐Ribeiro et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…This suite of methods and ideas has been applied to diverse research purposes: guiding discovery of populations of known (Bourg et al, 2005;Guisan et al, 2006) and unknown (Raxworthy et al, 2003) species; understanding distributional dynamics under past (Banks et al, 2008a;2008b) and future (Dormann, 2007;Anderson, 2013) climates; anticipating climate change impacts on agricultural (Fraga et al, 2013) and natural (Nabout et al, 2011) extraction; mapping invasion risk (Peterson, 2003;Jiménez-Valverde et al, 2011), pest distributions (Venette et al, 2010;Estay et al, 2014), and disease trasmission (Peterson, 2014); estimating population parameters (Tôrres et al, 2012;Lima-Ribeiro and DinizFilho, 2013;Thuiller et al, 2014), species richness (Wisz and Rahbeck, 2007;LimaRibeiro et al, 2013b), and community composition (Pellissier et al, 2012); analyzing biotic interactions (Anderson et al, 2002;Wheeler et al, 2015); illuminating patterns and processes of diversification and speciation (Silva et al, 2014); characterizing dispersal (Génard and Lescourret, 2013;Saltré et al, 2015); highlighting extinction (Nogués-Bravo et al, 2008;Lima-Ribeiro et al, 2013a); testing niche conservatism (Martínez-Meyer et al, 2004;Peterson and Nyári, 2007;Jakob et al, 2010) and phylogeographic hypotheses (Collevatti et al, 2013b;Alvarado-Serrano and Knowles, 2014); establishing historical refugia (Waltari et al, 2007;…”
Section: Potentiality Applicability and Relevancementioning
confidence: 99%
“…Climate and anthropogenic pressures are important drivers that shape biodiversity patterns and species distributions (Lorenzen et al., ) and so are potential threat factors (Lima‐Ribeiro, Nogués‐Bravo, Terribile, Batra, & Diniz‐Filho, ), contributing to the current conservation status of threatened species. However, their implications for conservation are quite different: although anthropogenic threats can be counterbalanced by laws or conservation measures, mitigation of climatic threats is a far more complex process, limited to intensive and economically expensive actions with unpredictable outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…ex situ conservation, risky translocations to theoretically suitable future areas; Cunningham, ; Dawson, Jackson, House, Prentice, & Mace, ; Weeks et al., ). Furthermore, the effects of anthropogenic and climatic drivers can be easily confounded, thereby hindering the assessment of their relative roles in taxon current conservation status, especially when analysing only current data that implies, at best, 50–60 years of continued surveillance of species occurrences (Bradshaw & Lindbladh, ; Li et al., ; Lima‐Ribeiro et al., ). Hence, it is crucial that the potential and current conservation status of threatened species are correctly assessed to facilitate the design and implementation of effective conservation and management plans, and to focus efforts on the most serious threat factors (Bolten et al., ).…”
Section: Introductionmentioning
confidence: 99%